Rapid duplexed detection of illicit drugs in wastewater using gold nanoparticle conjugated aptamer sensors - Mao, Kang; Ma, Jun; Li, Xiqing; Yang, Zhugen (Elsevier, 2019)
The abuse of illicit drug addiction is a worldwide public health and social problem. In this paper, we reported on a simple and rapid colorimetric biosensor for duplexed detection of methamphetamine (METH) and cocaine in a single assay. Gold nanoparticles (AuNPs) and Au@Ag NPs were synthesized and functionalized with DNA reporter probes (RPs) for METH and cocaine, respectively. The magnetic beads (MBs) were conjugated with two capture probes (CPs) respective to METH and cocaine. The respective RPs and CPs were designed to hybridize with each illicit drug-binding DNA aptamers through DNA-DNA hybridization, forming a sandwich structure. This MBs-based sandwich structure could be removed with an external magnetic field. However, due to the higher affinity of DNA aptamers with illicit drugs, the sandwich structure was disassembled when illicit drugs are introduced into the solution, leading to the colour changes of the supernatant. Utilizing a non-negative matrix factorization (NMF) algorithm to process the data, we demonstrated the ability of our biosensor for the simultaneous quantification of two illicit drugs. Under the optimal condition, our sensors were able to detect both METH and cocaine at the nM level with a wide dynamic range. This sensing platform provides a huge potential on drug consumption evaluation at the community level for wastewater-based epidemiology.
Keywords: Illicit drug of abuse; Wastewater-based epidemiology; Colorimetric biosensor